Integrated Silicon Optoelectronics - Zimmermann, Horst K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Integrated Silicon Optoelectronics synthesizes topics from optoelectronics and microelectronics. The book concentrates on silicon as the major base of modern semiconductor devices and circuits. Starting from the basics of optical emission and absorption, as well as from the device physics of photodetectors, the aspects of the integration of photodetectors in modern bipolar, CMOS, and BiCMOS technologies are discussed. Detailed descriptions of fabrication technologies and applications of optoelectronic integrated circuits are included. The book, furthermore, contains a review of the newest state of research on eagerly anticipated silicon light emitters. In order to cover the topics comprehensively, also included are integrated waveguides, gratings, and optoelectronic power devices. Numerous elaborate illustrations facilitate and enhance comprehension. This extended edition will be of value to engineers, physicists, and scientists in industry and at universities. The book is also recommended to graduate students specializing on microelectronics or optoelectronics.
Basics of Optical Emission and Absorption -- Theory -- Silicon Technologies and Integrated Photodetectors -- Optoelectronic Devices in Thin Crystalline Silicon Films -- Silicon Power Devices -- SiGe Photodetectors -- Detectors Based on Resonant Cavity -- III-V Semiconductor Materials on Silicon -- Silicon Light Emitters -- Integrated Optics -- Design of Integrated Circuits -- Examples of Optoelectronic Integrated Circuits.
Keywords: Physics; Electronics; Telecommunication; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Electronics and Microelectronics, Instrumentation; Communications Engineering, Networks